Kulturelle Vielfalt deutscher Literatur, Sprache und Medien Sommerschule für Alumni aus Osteuropa und der Welt 16. - 27. August 2009 - Casper-Hehne, Hiltraud; Schweiger, Irmy (Universitätsverlag Göttingen, 2009)
This book is a documentation of the alumni summer school"Kulturelle Vielfalt deutscher Literatur, Sprache und Medien". The collected articles explain the discussion about education in multi-cultural societies in providing an insight into intercultural didactics and intercultur in different texts and media.